Content production management of the Instagram account @erdegarage (BIS Humanities and Social Science, 2026)
The rapid development of social media has transformed how small business owners build relationships and interact with their customers. Instagram, as one of the most popular platforms in Indonesia, has become an essential medium for Micro, Small, and Medium Enterprises (MSMEs) to strengthen their brand identity and expand market reach. However, many MSMEs still face challenges in producing content that is engaging, consistent, and relevant to audience interests. This study aims to describe how content production management is implemented on the Instagram account @erdegarage. A qualitative approach was used, with data collected through in-depth interviews, direct observation, and content analysis of @erdegarage’s posts. The results show that effective content production management requires careful planning, strong team collaboration, and continuous evaluation based on audience engagement. @erdegarage applies a distinctive content strategy through visual storytelling, adaptation to digital trends, and a participatory approach. The use of cinematic visuals, consistent color tones, and customer cantered narratives enhances its premium image and builds emotional closeness with its followers. In conclusion, content production management at @erdegarage demonstrates that managing social media is not merely a technical process, but also a social and cultural practice that integrates creativity, authenticity, and audience interaction in shaping a brand’s digital identity.